Cross‐linking induced thermoresponsive hydrogel with light emitting and self‐healing property. Issue 8 (20th February 2019) - Shen, Jiafu; Wang, Xuemeng; An, Heng; Chang, Limin; Wang, Yong; Li, Wenjuan; Qin, Jianglei
ABSTRACT: Development of self‐healing hydrogels with thermoresponse is very important for artificial smart materials. In this article, the self‐healing hydrogels with reversible thermoresponses were designed through across‐linking‐induced thermoresponse (CIT) mechanism. The hydrogels were prepared from ketone group containing copolymer bearing tetraphenyl ethylene (TPE) and cross‐linked by naphthalene containing acylhydrazide cross‐linker. The mechanical property, light emission, self‐healing, and thermo‐response of the hydrogels were investigated intensively. With regulation of the copolymer composition, the hydrogels showed thermoresponse with the LCST varied from above to below body temperature. At the same time, the hydrogels showed self‐healing property based on the reversible characteristic of the acylhydrazone bond. The hydrogel also showed temperature‐regulated light emission behavior based on AIE property of the TPE unit. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2019, 57, 869–877 Abstract : The self‐healing hydrogels with reversible thermo‐responses were prepared through across‐linking‐induced thermoresponse (CIT) mechanism. The copolymer of TPE‐P(AM‐ stat ‐DAA) was synthesized through RAFT polymerization and cross‐linked by naphthalene containing diacylhydrazide to prepare self‐healing hydrogels. With regulation of the copolymer composition, the hydrogels showed thermo‐response with the LCST varied from above to below body temperature. The hydrogel also showed temperature‐regulated light emission behavior based on AIE property of the TPE unit.